2000
DOI: 10.2355/isijinternational.40.789
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth Process of Sticking Particles in Ferritic Stainless Steel.

Abstract: Nucleation and growth process of sticking particle in ferritic stainless steels was investigated using a twodisk type hot rolling simulator. The sticking behavior was strongly dependent on the surface roughness of a high speed steel roll (HSS) and the oxidation resistance of the ferritic stainless steels. A sticking occurrence was more sensitive for the steels containing higher chromium. There was a critical value which was found to be 3mm of scale thickness in the suppression of the sticking phenomenon. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…The sticking is more likely to occur at the temperature range in which the rolled steel is soft with low tensile strength, and also little amount of oxide scale is on the surface. The work of Jin et al [6] indicated that there was a critical oxide scale thickness (about 3.0 µm) in the suppression of the sticking phenomenon. The thicker oxide scale is desirable.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sticking is more likely to occur at the temperature range in which the rolled steel is soft with low tensile strength, and also little amount of oxide scale is on the surface. The work of Jin et al [6] indicated that there was a critical oxide scale thickness (about 3.0 µm) in the suppression of the sticking phenomenon. The thicker oxide scale is desirable.…”
Section: Resultsmentioning
confidence: 99%
“…15b, will increase the possibility of scratching the roll surface, and the lower the temperature the harder the oxide scale. Once there are more scratches on the roll surface, the sticking will become significant because these scratches might provide the nucleation site for the sticking particles, and the sticking particle grows more and more on the site as the rolling processes [6]. At a higher temperature, the thicker oxide scale (Fig.…”
Section: Inverse Calculation Of Coefficient Of Frictionmentioning
confidence: 99%
See 3 more Smart Citations